MiRNAs: A Powerful Tool in Deciphering Gynecological Malignancies - Duică, Florentina; Condrat, Carmen Elena; Dănila, Cezara Alina; Boboc, Andreea Elena; Radu, Mihaela Raluca; Xiao, Junjie; Li, Xinli; Creţoiu, Sanda Maria; Suciu, Nicolae; Creţoiu, Dragoş; Predescu, Dragoş-Valentin (Frontiers in Oncology, 2020)
Accumulated evidence on the clinical roles of microRNAs (miRNAs) in cancer prevention and control has revealed the emergence of new genetic techniques that have improved the understanding of the mechanisms essential for pathology induction and progression. Comprehension of the modifications and individual differences of miRNAs and their interactions in the pathogenesis of gynecological malignancies, together with understanding of the phenotypic variations have considerably improved the management of the diagnosis and personalized treatment for different forms of cancer. In recent years, miRNAs have emerged as signaling molecules in biological pathways involved in different categories of cancer and it has been demonstrated that these molecules could regulate cancer-relevant processes, our focus being on malignancies of the gynecologic tract. The aim of this paper is to summarize novel research ﬁndings in the literature regarding the parts that miRNAs play in cancer-relevant processes, speciﬁcally regarding gynecological malignancy, while emphasizing their pivotal role in the disruption of cancer-related signaling pathways.